Predictive, miniature co-extrusion of multilayered glass fiber-optic preforms - Bhowmick, Kaustav; Furniss, David; Morvan, Herve; Seddon, Angela B.; Benson, Trevor M. (Wiley, 2016)
A miniature co-extrusion technique, to produce a concentric multilayered glass fiber-optic preform of ~3 mm diameter, is modeled and experimentally demonstrated. A three-dimensional, incompressible, noncavitating, and nonisothermal Computational Fluid Dynamics (CFD) model, similar to one developed in our previous work, is used to predict the dimensions of an alternating four-layer glass stack feed required to produce the desired layer dimensions in a multilayered-glass preform extrudate, using a miniaturized and thus more economical co-extrusion. Strong agreement in the cross-sectional geometrical proportions of the simulated and experimentally obtained preform supports the prowess of the predictive modeling. Nevertheless, some small deviations between the simulated and experimentally obtained dimensions indicate topics for future rheological study. Performing the co-extrusion process under vacuum helps to minimize the inter-layer defects in the multi-layered fiber-optic preform. The miniature co-extrusion potentially removes the need for a postextrusion draw-down prior to fiber drawing, avoiding devitrification issues possible in non-oxide novel glass compositions.